Comparison of Gravimetric and Thermogravimetric Methods for Obtaining the Percentage of Residue Asphalt Bitumen Emulsion - Rodriguez Castro, Ellen (2025)
The characterization includes asphalt emulsions assay to quantify the distillation bitumen content. This test is performed for a long time, both in Costa Rica and other countries. It is a traditional and accurate method, which has been a very good choice for the recovery of residual asphalt bitumen emulsion, but is time consuming and requires the skills of the analyst to identify key moments of separation. Given that new technologies can be used to quantify the composition of asphalt emulsions, it intends to apply instrumental techniques thermogravimetric analysis. The first phase of the project is to determine the parameters to be used in a thermogravimetric analyzer (TGA) to get comparable results with the method of distillation. For which the temperature ramp and the heating rate in each of the samples are varied. Although the results show no statistically significant differences, the effect of parameter changes in the thermogravimetric analysis results in perceived. The results show that it is possible to use the instrumental thermogravimetric analysis to determine the percentage of asphalt emulsion residue, but also allows establishing the conditions to be defined as part of a process of analysis should be selected according to the results heating rates 10 ° C / min or less than 5 ° C / min. It also determined that rates of warming modulated not give good results. In the next phase of the project the methods will be compared using emulsions manufactured in the laboratory, considering the parameters defined in this phase.